The Effect of Frankel’s Stabilization Exercises and Stabilometric Platform in the Balance in Elderly Patients: A Randomized Clinical Trial - Mańko, Grzegorz (Medicina (Kaunas), 2019)
Background and Objectives: Every year, older people are becoming a larger part of the population. In a couple of years medicine is going to struggle with specific disorders and their consequences, where one of them are falls. Fall prevention involves a use of strengthening exercises, equivalent exercises, stabilometric platforms, and special exercise programs. Almost the entire brain is involved in maintaining correct balance. Reduction of a volume of gray matter negatively affects balance. Single exercise sessions do not significantly improve balance. In order to achieve satisfactory results at least 10 training sessions are required. The aim of this study is to determine if there is a correlation between a risk of falls, gender, and a risk of falls and the age of the subjects. Another reason to conduct that research was to assess the effectiveness of Frankel’s exercises and training of using the stabilometric platform in rehabilitation, which aims to reduce the risk of falls among elderly people. Materials and Methods: The study involved 40 elderly patients referred for physiotherapy to a rehabilitation center. The patients were divided into two groups of 20 people. In experimental group 1 (C) Frankel’s stabilization exercises were used; in experimental group 2 (E) a stabilometric platform was used. The correlation between the risk of falls and age as well a risk of falling and the gender of the examined persons was taken into consideration. The effect of therapy that uses stabilization exercises and the stabilometric platform on the risk of falls in the examined persons was assessed using the Tinetti scale. Clinical control was performed using the Tinetti scale, before and after a two-week rehabilitation period. Results: The study showed no correlation between the degree of risk of falling and age, and between the risk of falling by the elderly and gender. There were also changes in the results obtained by patients after using the training, both with the use of Frankel’s stabilization exercises as well as with the use of the stabilometric platform. Patients using the dynamometric platform obtained higher results in the Tinetti test after treatment. Conclusions: In the examined sample, no correlation was found between the risk of falls and age as well as the risk of falls and gender. Both Frankel’s exercises and training with the use of the stabilometric platform were effective in a rehabilitation program aimed at reducing the risk of falls among the elderly.